A phase II trial of anlotinib plus EGFR-TKIs in advanced non-small cell lung cancer with gradual, oligo, or potential progression after EGFR-TKIs treatment (CTONG-1803/ALTER-L001) - Hua-Jun Chen; Hai-Yan Tu; Yanping Hu; Yun Fan; Guowu Wu; Shundong Cang; Yi Yang; Nong Yang; Rui Ma; Gaowa Jin; Ximing Xu; Anwen Liu; et al. (Journal of Hematology & Oncology)
Abstract Background The study is to evaluate the efficacy and safety of combined anlotinib and EGFR-tyrosine kinase inhibitors (TKIs) in patients with advanced non-small cell lung cancer (NSCLC) who had gradual, oligo, or potential progression after previous EGFR-TKIs treatment. Methods We conducted an open-label, single-arm, multicenter, phase II trial in China. Eligible patients were 18–75 years old with histologically or cytologically confirmed NSCLC who were EGFR mutation positive and showed gradual, oligo, or potential progression after EGFR-TKIs. Anlotinib (12 mg/day) was administered orally for 2 weeks and then off 1 week in a 3-week cycle. EGFR-TKIs were continue used. The primary endpoint was progression-free survival (PFS). The secondary endpoints included 6- and 12-month PFS rate, objective response rate (ORR), disease control rate (DCR), overall survival (OS) and safety. Results From July 2019 to December 2022, 120 patients were enrolled. The median PFS (mPFS) was 9.1 months (95% CI 6.8–11.7). The PFS rates at 6 and 12 months was 68.5% and 38.8% respectively. For 86 patients with first-line 1st /2nd generation EGFR-TKIs, the mPFS was 9.2 months (95% CI 6.7–12.6). For 32 patients with first-line 3rd generation EGFR-TKIs, the mPFS was 10.3 months (95% CI 6.1–13.3). Overall ORR and DCR were 6.7% (95% CI 2.9–12.7) and 87.5% (95% CI 80.2–92.8), respectively. 52.5% of patients had grade 3 or higher treatment-emergent adverse events (TEAEs). Conclusion Anlotinib in combination with continuation of EGFR-TKIs prolonged the clinical benefit of EGFR-TKIs, demonstrating favorable survival outcomes and manageable toxicity in NSCLC treated with EGFR-TKIs and had specific progression modes, such as gradual progression. Trial registration NCT04007835.